Analisis Yuridis Perlindungan Anak dalam Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan Terkait Pencegahan Perkawinan Dibawah Umur - Barokah, Shafa Alifia; Ubaidillah, Luthfian (Indonesian Journal of Law and Justice, 2024)
The aim of this research is to find out what form of child protection is in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage Regarding the Prevention of Underage Marriage? The type of research used in this research is normative juridical research using a statutory approach and a conceptual approach. The results of this research are child protection related to procedures for preventing underage marriages that have been stated in a law. -Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, namely by adding provisions, namely that the age of the male and female must both be 19 years old and if the child has entered into a marriage, it must be based on the following reasons. urgent reasons accompanied by sufficient evidence before the court, if a child cannot fulfill the requirements as stated above, then a request for marriage dispensation cannot be made in a religious court and the judge will reject the marriage dispensation because it is not in accordance with terms and conditions in accordance with the laws and regulations in force in Indonesia.